PREMISE PSIHOLOGICE ŞI PEDAGOGICE ALE GHIDĂRII ÎN CARIERĂ - USM ADMIN (Moldova State University, 2012)
Career guidance, as part of the educational process is necessary and important because it is based on psychological and pedagogical assumptions. Psychological premises are outlined in the psychology of work that expresses the relationship between employee and his or her employment context. In a relatively new aspect this relationship is expressed in terms of technological progress. Psychological personality defines personality as both an internal and external relational system. From the pedagogical perspective, education is regarded as an essentially phenomenon placed at base of world evolution. Rapport between need and demand for education makes career guidance be required.